Facet-Dependent Catalytic Activity of MnFe Prussian Blue Analogues in Peroxymonosulfate-Activated System for Efficient Degradation of Acetamiprid - Ruonan Guo; Beidou Xi; Changsheng Guo; Heng Zhang; Long Chen; Liu, Wen; Ningqing Lv; Jian Xu (ACS ES&T Water, 2023)
MnFe Prussian blue analogues (MnFe PBAs) were fabricated for acetamiprid degradation with peroxymonosulfate (PMS) as an oxidant. MnFe PBAs (200) are the most active facets for PMS activation due to the superior chemisorption affinity and electron-transfer ability. Density functional theory calculation verified that Mn(III) served as an electron donor and acceptor to adjust the electron density between Fe and Mn, which played a crucial role in the high activation performance of MnFe PBAs (200). PBA lattice (−C═N) did not exhibit direct PMS activation capability in this system, which differed from previously reported Fenton counterparts. Based on the electronic localization function calculation and probe experiments, the O–O of HSO5– was broken, and the bonds of PBA could be restored during the activation reaction, leading to the continuous generation of reactive oxygen species in the MnFe PBAs/PMS system. Transformation product studies indicated that the oxidized products were primarily the result of aromatic hydroxylation, N–C bond cleavage, azo reaction, and so forth, achieving the mineralization and ecotoxicity mitigation of acetamiprid efficiently. Findings in this study provided new insights into developing advanced facet-dependent catalysts to activate PMS for the efficient degradation of emerging contaminants in the aqueous environment.